HOW NON-CURRICULAR ARTS ARE USED TO STRENGTHEN THE SOCIAL STATUS OF ENGINEERS: Received: 28th March 2024 Revised: 02nd May 2024 Accepted: 02nd April 2024 - Dr. Mohammed Algarni (PEOPLE: International Journal of Social Sciences, 2024)
The paper discusses the concept of using non-curricular arts to strengthen the social status of engineers by expanding skillset and perception, building bridges, and connections. While there’s no definitive answer of how non-curricular arts are used to strengthen the social status of engineers, the study presents some artistic ways of engagement that can impact engineers’ social standing by demonstrating creativity and innovation, communication and storytelling, collaboration, and empathy. The study shows that the impact of non-curricular arts on engineers’ social status depends on individual engagement, societal context, and how the artistic pursuit is perceived. While not a guaranteed formula, actively engaging in diverse artistic mediums can certainly contribute to a more well-rounded, respected, and connected image of engineers within society. Finally, the paper presents a comprehensive overview of how non-curricular arts can potentially influence the social status of engineers.